2016
DOI: 10.1111/jpn.12473
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Chinese herbal mixture on performance, egg quality and blood biochemical parameters of laying hens

Abstract: The aim of the study was to evaluate the effect of Chinese herbal mixture (CHM) in laying hen diets on performance, egg quality and egg nutrition components, as well as selected blood biochemical parameters. A total of 270 Lohmann Brown laying hens, 24 week of age, were randomly distributed into three dietary treatments and fed for 6 week. The CHM was used at the levels of 0%, 0.5% and 1.0% in the diets of the control and two treatment groups respectively. Each dietary treatment was divided into five replicate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 57 publications
(67 reference statements)
2
15
0
Order By: Relevance
“…This study showed no significant difference in yolk color and eggshell properties (color, breaking strength, and thickness) among the dietary treatments. This is consistent with the previous reports that indicated no alteration in most of the egg quality traits in laying hens fed S. chinensis [ 32 ] and pine needles [ 33 ]. Li et al [ 32 ] reported that egg weight, eggshell thickness, egg white height, HU, and eggshell breaking strength had not changed in a study that fed 24-wk-old Lohmann Brown laying hens with 0.5% to 1% Chinese herbal mixture (containing 70% pine needles and 30% Artemisia annua ) in the diet.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This study showed no significant difference in yolk color and eggshell properties (color, breaking strength, and thickness) among the dietary treatments. This is consistent with the previous reports that indicated no alteration in most of the egg quality traits in laying hens fed S. chinensis [ 32 ] and pine needles [ 33 ]. Li et al [ 32 ] reported that egg weight, eggshell thickness, egg white height, HU, and eggshell breaking strength had not changed in a study that fed 24-wk-old Lohmann Brown laying hens with 0.5% to 1% Chinese herbal mixture (containing 70% pine needles and 30% Artemisia annua ) in the diet.…”
Section: Discussionsupporting
confidence: 93%
“…This is consistent with the previous reports that indicated no alteration in most of the egg quality traits in laying hens fed S. chinensis [ 32 ] and pine needles [ 33 ]. Li et al [ 32 ] reported that egg weight, eggshell thickness, egg white height, HU, and eggshell breaking strength had not changed in a study that fed 24-wk-old Lohmann Brown laying hens with 0.5% to 1% Chinese herbal mixture (containing 70% pine needles and 30% Artemisia annua ) in the diet. Kim and Paik [ 33 ] also indicated no changes in eggshell strength, eggshell thickness, eggshell color, egg yolk, and HU when 66-wk-old Hy-line Brown hens were fed 0.2% plant extracts, including turmeric, Angelica gigas , S. chinensis , Glycyrrhiza glabra , and Levisticum officinale .…”
Section: Discussionsupporting
confidence: 93%
“…Knowledge of bird hematology is a useful diagnostic tool in veterinary medicine ( Merck Manual, 2012 ). Hematological values are commonly used as physiological indicators of health in birds housed in cage systems and can be used detect stress caused by various factors, such as environmental, nutritional, and pathological aspects ( Toghyani et al., 2010 , Li et al., 2015 ). Overall, hematological indices in all treatment groups were observed to be within the anticipated ranges for healthy layers ( Merck Manual, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…Among a variety of reduction technologies, extraction of cholesterol by critical carbon dioxide seems one of the excellent procedures [157]. Egg cholesterol can be reduced by feeding specific compounds, such as phytosterols or polyphenols, to laying hens, but the extent of reduction is approximately 10% [158,159], except for the 25% reduction of cholesterol in one report using special Chinese medicinal herbs [160]. However, both approaches seem not cost-effective at present.…”
Section: Rebuttal To "Innocent Theory" Of Egg Consumptionmentioning
confidence: 99%